2005
DOI: 10.1186/gb-2005-6-9-r73
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cyanobacterial non-coding RNAs by comparative genome analysis

Abstract: Identification of cyanobacterial non-coding RNAs

The first genome-wide and systematic screen for non-coding RNAs (ncRNAs) in cyanobacteria. Several ncRNAs were computationally predicted and their presence was biochemically verified. These ncRNAs may have regulatory functions, and each shows a distinct phylogenetic distribution.

Abstract Background: Whole genome sequencing of marine cyanobacteria has revealed an unprecedented degree of genomic variation and streamlining. With a size of 1.66 megabase-pair…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 66 publications
1
66
1
Order By: Relevance
“…Intergenic regions may give rise to sRNAs, another type of important regulatory factors with an important role in physiological adaption and as a driver of interstrain divergence in bacteria, including cyanobacteria (33,34,(49)(50)(51). Studies of the filamentous and nitrogen-fixing cyanobacterium Nodularia spumigena CCY9414 genome and its acclimation to stress conditions point further sRNAs crucial role in cell functioning, especially in gene expression regulation (13,52).…”
Section: Resultsmentioning
confidence: 99%
“…Intergenic regions may give rise to sRNAs, another type of important regulatory factors with an important role in physiological adaption and as a driver of interstrain divergence in bacteria, including cyanobacteria (33,34,(49)(50)(51). Studies of the filamentous and nitrogen-fixing cyanobacterium Nodularia spumigena CCY9414 genome and its acclimation to stress conditions point further sRNAs crucial role in cell functioning, especially in gene expression regulation (13,52).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the vast majority of data on bacterial riboregulators stem from the analysis of enterobacteria, whereas a single systematic search exists for noncoding RNAs in cyanobacteria (23). It is very likely that cyanobacteria, which grow under extremely diverse environmental conditions and have an evolutionary history of Ͼ3 billion years, have developed a complex RNA-based regulatory mechanism to deal with changes in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blots and hybridizations were performed as described in ref. 23. Verification of equal loading was achieved by measurement of RNA concentrations, direct comparison of rRNA band intensities after staining by ethidium bromide, or hybridization with a 16S rRNA probe.…”
Section: Methodsmentioning
confidence: 99%
“…These processes include regulating the expression of outer membrane proteins (Guillier and Gottesman 2006;Valentin-Hansen et al 2007), iron homeostasis (Massé et al 2005Vecerek et al 2007), quorum sensing (Lenz et al 2005;Tu and Bassler 2007), and bacterial virulence (Romby et al 2006;ToledoArana et al 2007). For example, it has been found that MicF, a 93-nt sRNA, can inhibit the expression of OmpF, an outer membrane protein (Axmann et al 2005;Vogel and Papenfort 2006;Prévost et al 2007;Urban et al 2007;Song et al 2008;Desnoyers et al 2009;Papenfort et al 2009). Although the functions of some sRNAs have been obtained, there are still many sRNAs with functions waiting to be elucidated.…”
Section: Introductionmentioning
confidence: 99%